Design, fabrication and performance test of die-punch set for powder compaction process - Logatarsan, Chandran (2017)
This study is mainly about the fabrication of die-punch set using two different metals; Tool Steel SKD61 and Hardened Steel SKDll. Powder compaction processes are well known in many industries nowadays and this process requires a die-punch set. Thus through this study, the performance comparison between both type of die-punch are also obtained. Hardened Steel SKD 11 is commonly used in many industries. Thus, comparison between the two different types of die-punch is done to observe which diepunch has better performance. Fabrication of a die-punch set requires a proper design to be processed first. Once the design selection with a suitable dimension and tolerance are made, then the fabrication process can start. Few machining operations are done to ensure a successful fabrication of the die-punch set. The fittings of each part of the diepunch set are made aligned. Performance testing of the die-punch set is done by producing green compacts through powder compaction method. Before this green compacts are made, the metal powders are prepared and mixed well based on the compositions that needed in this research project. A total of three different metal powder compositions are tested. Once the compaction is done, the green compacts are sintered. Then, the sintered compacts are tested for their hardness. Hardness test is done to show which die-punch set can produce a metal ceramic compact with a better hardness.